Adipose tissue: A natural resource for multipotent mesenchymal stem cells with potential translation to trigerminal layers - Bhaskar Vyas; Atul Shah; Anant Marathe; Rajni Vyas; Ramesh Bhonde (Indian Journal of Plastic Surgery)
Background: The article reports basic science research that establishes that adipose tissue (AT)-derived mesenchymal stem cells (MSCs) have a potential to transgerminal translation. Study Design: MSC confirmation was obtained by phenotypic spindle-shaped cells as well as with four positive and three negative markers. The translineage translation of adipose-derived MSCs (ADMSCs) was established. Materials and Methods: The lipoaspirate was subjected to enzymatic digestion with collagenase. Stromal vascular factor (SVF) was isolated. With two passages, pure culture of ADMSCs was obtained. They were translated to all the three germinal layers. Results: AT-derived SVF contains ~30% MSCs. They are capable of being translated into endoderm, mesoderm and ectoderm. Conclusion: AT is a rich source for MSCs, with immense research possibilities for regeneration and rejuvenation.